Corinnella lourii, a rare new species of Baetidae (Ephemeroptera) from central Brazil - Salles, F.f.; Victoriano, A.s.; Boldrini, R.; Cabette, H.r.s. (Zootaxa, 2017)
A new species of the rare genus Corinnella is described based on nymphs from the Rio Pindaíba, a river located close to the Cerrado - Amazonian border. The new species is more related to C. eximia than to C. thomasi, but can be distinguished from them by the following combination of characters: 1) distomedial emargination of labrum broad and with very small process; 2) maxillary palp 2.0× length of galea-lacinia; 3) posterior margin of terga I–IX with pointed spaced spines; 4) claws with four denticles.